2002
DOI: 10.1097/00005131-200208000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Maisonneuve Fracture Associated With a Bimalleolar Ankle Fracture–Dislocation: A Case Report

Abstract: The Maisonneuve fracture consists of a proximal fibular fracture with associated syndesmotic ligament disruption and injury to the medial ankle structures. The accepted mechanism of injury is an external rotation force applied to the ankle with the foot in either supination or pronation. Because most Maisonneuve fractures involve complete syndesmotic disruption, operative treatment is usually indicated. A case report is presented of an unusual fracture pattern-i.e., that of a distal fibular fracture with later… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
10
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 5 publications
1
10
0
Order By: Relevance
“…However numerous injuries deviating from the classical fracture scheme are described, like the combination with lateral ankle dislocation, showing a triplane fracture pattern in the adolescent or in association with an additional distal fibula fracture. 79 …”
Section: Discussionmentioning
confidence: 99%
“…However numerous injuries deviating from the classical fracture scheme are described, like the combination with lateral ankle dislocation, showing a triplane fracture pattern in the adolescent or in association with an additional distal fibula fracture. 79 …”
Section: Discussionmentioning
confidence: 99%
“…Levy et al reported a case of an avulsion injury of the medial malleolus with disruption of the deltoid ligaments and dislocation of the proximal tibiofibular joint [7]. Furthermore there are few reports about distal fibular fractures with associated proximal fibular fracture [5,6]. As a dislocation of the proximal fibula is a rare entity the importance of precise history making and careful standardized examination with a high level of clinical suspicion cannot be overestimated [16].…”
Section: Discussionmentioning
confidence: 99%
“…3,5,6,[18][19][20] Few of the published case studies of ankle dislocation and fibula fracture are sport related. [7][8][9][10][11][12]14,[20][21][22][23][24] Of those cases, few authors 25 discuss the occurrence in high-level football athletes.…”
mentioning
confidence: 99%
“…External rotation of the ankle, paired with either pronation or supination, can place the ankle joint in a vulnerable position for dislocation or fracture (or both). 1,4,13,16,18,20,22 Many injury classification methods use the mechanism of injury to determine the extent of damage. 5,17,18 The Weber classification method uses the level of fibular fracture to classify the injury.…”
mentioning
confidence: 99%
See 1 more Smart Citation